Dissipative particle dynamics study of solvent mediated transitions in pores decorated with tethered polymer brushes in the form of stripes - Ilnytskyi, J.M.; Sokolowski, S.; Patsahan, T. (Condensed Matter Physics, 2013)
We study self-assembly of a binary mixture of components A and B confined in a slit-like pore with the walls modified by the stripes of tethered brushes made of beads of a sort A. The emphasis is on solvent mediated transitions between morphologies when the composition of the mixture varies. For certain limiting cases of the pore geometry we found that an effective reduction of the dimensionality may lead to a quasi one- and two-dimensional demixing. The change of the environment for the chains upon changing the composition of the mixture from polymer melt to a good solvent conditions provides explanation for the mechanism of development of several solvent mediated morphologies and, in some cases, for switching between them. We found solvent mediated lamellar, meander and in-lined cylinder phases. Quantitative analysis of morphology structure is performed considering brush overlap integrals and gyration tensor components.